Online learning for EFL students in Palestinian universities during corona pandemic: Advantages, challenges and solutions - Mohammed Farrah; Ghaida Hatem al-Bakry (Universitas Kuningan, 2020)
This study attempts to examine the perceptions of EFL students in Palestinian universities about online learning advantages, challenges, and solutions during Corona pandemic. Moreover, it aims to highlight the efficiency of online learning as an educational system which can be relied on to achieve goals of high educational institutions. The researchers investigated the current situation of online learning in Palestinian universities during the COVID-19 pandemic using a questionnaire. In the questionnaire, the participants were 191 students (161 females and 30 males), and all of the participants have tried the online learning experience during this pandemic. 33% of them took online courses before, while 67% did not. The questionnaire was posted on 6 English clubs’ websites of 6 Palestinian universities: Birzet University, An-Najah National University, Bethlehem University, Hebron University, Al-Quds University, and Palestine Ahliya University. The investigation was concerned in pointing out the challenges facing the students during their online courses, in addition to finding out solutions in terms of involving students in the assessment process. The findings confirmed the need to conduct changes and improvements regarding the implementation of e-learning in the educational process in order to help high ministries of education achieve more real success in spreading knowledge. The researchers concluded that there should be massive efforts in improving the technological infrastructure besides holding good training programs for both students and teachers.